PENGARUH STATUS KEPEGAWAIAN, HUBUNGAN INTERPERSONAL, PENGEMBANGAN KARIR, DAN KETIDAKJELASAN PERAN TERHADAP GEJALA STRES PADA KARYAWAN PT BANK DANAMON CABANG BALIKPAPAN, KALIMANTAN TIMUR - Irdiana Irdiana (Fakultas Ekonomi Universitas Borobudur, 2013)
The aimed of the research was determined the level of work stress of PT. Bank Danamon employees, Balikpapan Branch, East Kalimantan psychologically, physically and total. Analyzing the influence of generating stress factors on employment status, interpersonal relationship, career development and role ambiguity. 60 random respondents assigned. They were permanent and temporary employees. Result of analysis showed that employee work stress was not influenced by employment status, but interpersonal relationship, career development and role ambiguity influenced stress sympthoms psychologically, physically and total. The amount of influence of each variable differ each other, while interpersonal relationship significantly influenced on the emerge of stress sympthoms. Keyword: Work stress, Employment status, Interpersonal relationship, career development, role ambiguity